Sistema informático para la optimización de la gestión documentaria en la dirección de responsabilidad social - UNAP – 2024 - Rinaby Torres, Edgar Alexander (2025)
The Social Responsibility Department (DRS) of the National University of the Peruvian Amazon needs to improve its document management by implementing an IT system that improves document recording, the preparation of reliable reports, and reduces the time associated with these processes. This study aims to evaluate the impact of the IT system on the document management of the National University of the Peruvian Amazon DRS 2024, analyzing its effect on document recording, the generation of reliable reports, and execution times. The research has a quantitative and applied approach, with a longitudinal trend design. Techniques such as observation, document analysis, and observation sheets were employed. For statistical analysis, SPSS version 27 was used, applying the Chi-square test for homogeneity for categorical variables (document recording and preparation of reliable reports) and the Mann-Whitney U test for quantitative variables (recording times and generation of reliable reports), with a significance level of 5%. The results show a significant improvement: document registration increased from 44% to 100%, reliable report generation increased from 9.1% to 100%, and execution times were reduced. It is concluded that the implementation of the IT system optimizes document management at the DRS National University of the Peruvian Amazon 2024.